KARAKTERISTIK KEJADIAN HIPEREMESIS GRAVIDARUM (HEG) DI RUMAH SAKIT PALEMBANG TAHUN 2021 - Sri Handayani (Jurnal Kesehatan dan Pembangunan, 2022)
Maternal mortality according to WHO (World Health Organization, 2014) is around 830 women die from complications of pregnancy or childbirth worldwide every day. Hyperemesis Gravidarum is excessive nausea and vomiting in pregnant women to the point of interfering with daily work because it generally becomes worse due to dehydration. The purpose of this study was to determine the characteristics of the incidence of hyperemesis gravidarum at Muhammadiyah Hospital Palembang in 2021. The research method used a quantitative research type that was descriptive analytic with a retrospective approach. The population is pregnant women who are treated in the obstetrics room as many as 828 people with a total sample of 270 people taken by means of Simple Random Sampling. The results of the study based on the chi-square test showed that there was a relationship between the incidence of hyperemesis with maternal age (p value = 0.041), parity (p value = 0.043), education (p value = 0.022), and occupation (p value = 0.001). Suggestions for Palembang Muhammadiyah Hospital to increase counseling about hyperemesis gravidarum in pregnant women so that pregnant women can easily recognize the signs and symptoms of HEG.